The mathematical model and program for Calculation of heat exchange at continuous casting of a strip in the “wheel-belt” mould - E. F. Baranovski; V. A. Pumpur (Литьë и металлургия)
Is given the 2-D mathematical description of heat exchange in castings and moulds. The program for computation of the temperature fields and strip solidification kinetics is presented